Comparison of the medium cutoff dialyzer and postdilution hemodiafiltration on the removal of small and middle molecule uremic toxins - Chang Seong Kim; Soo Yeon Joo; Hong Sang Choi; Eun Hui Bae; Seong Kwon Ma; Soo Wan Kim (The Korean Society of Nephrology, 2023)
Background The medium cutoff (MCO) dialyzer increases the removal of several middle molecules more effectively than high-flux hemodialysis (HD). However, comparative data addressing the efficacy and safety of MCO dialyzers vs. postdilution hemodiafiltration (HDF) in Korean patients are lacking. Methods Nine patients with chronic HD were included in this pre-post study. Patients underwent HD with an MCO dialyzer for 4 weeks, followed by a 2-week washout period using a high-flux dialyzer to minimize carryover effects, and then turned over to postdilution HDF for 4 weeks. Reduction ratios and differences in the uremic toxins before and after dialysis were calculated from the MCO dialysis, postdilution HDF, and high-flux HD. In the in vitro study, EA.hy926 cells were incubated with dialyzed serum. Results Compared to postdilution HDF, the MCO dialyzer achieved significantly higher reduction ratios for larger middle molecules (myoglobin, kappa free light chain [κFLC], and lambda FLC [λFLC]). Similarly, the differences in myoglobin, κFLC, and λFLC concentrations before and after the last dialysis session were significantly greater in MCO dialysis than in postdilution HDF. The expression of Bax and nuclear factor κB was decreased in the serum after dialysis with the MCO dialyzer than with HDF. Conclusion Compared with high-volume postdilution HDF, MCO dialysis did not provide greater removal of molecules below 12,000 Da, whereas it was superior in the removal of larger uremic middle molecule toxins in patients with kidney failure. Moreover, these results may be expected to have an anti-apoptotic effect on the human endothelium.